The Evolution of Cybercrime in the Digital Era: Legal and Security Implications - Destia Herlisya (CV. Tripe Konsultan, 2025)
The evolution of cybercrime in the digital era has created significant threats and challenges in the fields of law and global security. These threats not only jeopardise individuals but also damage critical infrastructure and cause substantial economic losses. This research aimed to explore the evolution of cybercrime in the digital age, understand its legal implications, and analyse the challenges arising in maintaining cybersecurity at both global and national levels. The study adopts a literature analysis approach, collecting data from journal articles, books, official reports, as well as sources from international organisations and government agencies involved in cybersecurity. The subject of this research includes a literature review of various publications related to cybercrime, legal policies, and regulations implemented to combat cyber threats. The findings of this research show that cybercrime now involves attacks on critical infrastructure and large-scale data theft, with its impact expected to reach 10.5 trillion USD by 2025. The study suggests updating cybersecurity regulations, enhancing international cooperation, and strengthening digital literacy as preventive measures to mitigate cybercrime threats.